THE INFLUENCE OF FINANCIAL LITERACY AND CONVENIENCE ON INTEREST IN USING QUICK RESPONSE CODE INDONESIAN STANDARD (QRIS) IN FINANCIAL TRANSACTIONS - Irsyad Azis Ardiansyah; Lella Anita; Northa Idaman; Atika Lusi Tania (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study aims to analyze the influence of financial literacy—as a representation of accounting understanding—and ease of use on the interest in using the Quick Response Code Indonesian Standard (QRIS) in financial transactions among Sharia Accounting students of IAIN Metro. A quantitative approach is applied through data collection with a questionnaire that has previously been tested for validity and reliability in order to obtain representative information.Methods: Data analysis was carried out using normality, multicollinearity, heteroscedasticity, and multiple linear regression tests to test the partial and simultaneous effects of the research variables. The results showed that financial literacy had a significant positive effect on the interest in using QRIS, with a regression coefficient of 0.257, while ease of use had a more dominant effect with a coefficient of 0.492. Simultaneously, the two variables were able to explain 30.4% of the variation in interest in using QRIS.Results: These findings indicate that increasing understanding of financial concepts can boost confidence in adopting QRIS, while simplifying the user interface plays an important role in accelerating digital transactions. This study suggests that educational institutions and financial technology developers collaborate to integrate financial literacy education with the development of user-friendly systems, so that they can support the creation of more efficient and secure financial transactions. Keywords: QRIS, Financial Literacy, Ease of Use, Interest